Low-residual-alkali high-nickel positive electrode material and preparation method thereof, positive electrode and battery
By mixing and sintering the high-nickel ternary cathode material with ammonium phosphomolybdate to form a low-residual alkali high-nickel cathode material, the problem of residual alkali in the high-nickel cathode material is solved, and the electrochemical performance and battery life are improved.
Patent Information
- Application Number
- CN202510286874.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During use, high-nickel ternary cathode material is prone to react with water and CO2 in the air, forming residual alkali, resulting in battery pulping, coating process and safety problems, and direct water washing will damage the surface structure of the material.
By mixing and stirring the ordinary high-nickel ternary cathode material with an ammonium phosphomolybdate suspension, the solid in the solid-liquid mixture is extracted and sintered under aerobic conditions to form a low-residual alkali high-nickel cathode material. After sintering, ammonium phosphomolybdate forms a lithium molybdate conductor layer, which increases the transmission speed of lithium ions and protects the positive electrode material.
It has achieved the reduction of residual alkali on the surface of high-nickel positive electrode material, improved the electrochemical performance of the material, extended the battery life, and reduced the generation of side reactions.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a low-residual-alkali-high-nickel positive electrode material and a preparation method thereof, a positive electrode and a battery. Background Art
[0002] High-nickel ternary positive electrode materials have advantages such as higher specific capacity and specific energy. However, high-nickel ternary positive electrode materials also have obvious disadvantages. For example, the higher the Ni content, the easier it is to react with water and CO2 in the air to generate LiOH and Li2CO3, resulting in the so-called high surface residual alkali. The presence of residual alkali can easily cause battery pulping, coating process and safety problems. Direct water washing can effectively remove alkaline impurities such as LiOH and Li2CO3 on the surface of high-nickel positive electrode materials, but it will destroy the surface structure of the material. If combined with water washing and coating treatment, it can not only effectively reduce alkali, but also improve the cycle performance of the battery. Because the coating layer can not only act as an ion conductor layer to accelerate the transmission of lithium ions, but also act as a physical barrier to inhibit side reactions between the positive electrode material and the electrolyte, it can not only increase the specific capacity but also extend the life of the battery.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a low residual alkali high nickel positive electrode material and a preparation method thereof, a positive electrode and a battery, aiming to improve at least one of the problems mentioned in the background technology.
[0005] The present invention is achieved in that: In a first aspect, an embodiment of the present invention provides a method for preparing a low residual alkali high nickel positive electrode material, comprising: The common high-nickel ternary cathode material and the ammonium phosphomolybdate suspension are mixed and stirred for 1 to 5 minutes to obtain a solid-liquid mixture, and then the solid in the solid-liquid mixture is extracted; The obtained solid is sintered under oxygen conditions to obtain a low residual alkali and high nickel positive electrode material; The chemical formula of ordinary high-nickel ternary positive electrode materials is LiNi x Co y Mn 1-x-y O2, where x ≥ 0.8, 0 < y ≤ 0.2; The chemical formula of ammonium phosphomolybdate is (NH4)3[PMo 12 O 40 ·6H2O]; The mass ratio of ammonium phosphomolybdate to common high-nickel ternary cathode material is 3~12:1000; The mixing and stirring time of ordinary high-nickel ternary positive electrode material and ammonium phosphomolybdate suspension is 1 to 5 minutes.
[0006] In an optional embodiment, the method of extracting the solid in the solid-liquid mixture includes: obtaining filter material by filter pressing, and drying the filter material.
[0007] In an optional embodiment, the pressure of the filtration is 0.3-0.5 MPa, and the filtration time is 1-10 min; Optionally, the drying temperature is 100-150°C.
[0008] In an optional embodiment, the sintering temperature is 500-600° C. and the sintering time is 5-10 hours.
[0009] In a second aspect, the present invention provides a low residual alkali high nickel positive electrode material, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0010] In a third aspect, the present invention provides a positive electrode, the active component of which includes the positive electrode material as described in the foregoing embodiment.
[0011] In a fourth aspect, the present invention provides a battery, comprising the positive electrode according to the aforementioned embodiment.
[0012] The present invention has the following beneficial effects: On the one hand, the residual alkali on the surface of the high-nickel positive electrode is reduced by the ammonium phosphomolybdate suspension, and on the other hand, the positive electrode surface will be covered by ammonium phosphomolybdate after filter pressing. After sintering, the ammonium phosphomolybdate will form a lithium molybdate ion conductor layer on the positive electrode surface, which accelerates the transmission of lithium ions at the interface, and can protect the contact between the ternary material and the electrolyte, reducing the generation of side reactions. Therefore, the preparation method provided by the present invention can simultaneously realize the construction of the alkali reduction and surface protection functional layer, improve the electrochemical performance of the material, and have better electrochemical performance than the existing preparation method to obtain the same type of positive electrode material. DETAILED DESCRIPTION
[0013] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0014] The low residual alkali and high nickel positive electrode material and its preparation method, positive electrode and battery provided in the embodiments of the present invention are described in detail below.
[0015] The method for preparing a low residual alkali high nickel positive electrode material provided by an embodiment of the present invention comprises: A common high-nickel ternary positive electrode material is mixed and stirred with an ammonium phosphomolybdate suspension to obtain a solid-liquid mixture, and then a solid in the solid-liquid mixture is extracted; The obtained solid is sintered under oxygen conditions to obtain a low residual alkali and high nickel positive electrode material; The chemical formula of ordinary high-nickel ternary positive electrode materials is LiNi x Co y Mn 1-x-y O2, where x ≥ 0.8, 0 < y ≤ 0.2; The chemical formula of ammonium phosphomolybdate is (NH4)3[PMo 12 O 40 ·6H2O], the structural formula is: ; The mass ratio of ammonium phosphomolybdate to common high-nickel ternary cathode material is 3~12:1000; The mixing and stirring time of ordinary high-nickel ternary positive electrode material and ammonium phosphomolybdate suspension is 1 to 5 minutes.
[0016] The preparation method provided in the embodiment of the present invention, on the one hand, reduces the residual alkali on the surface of the high-nickel positive electrode through the ammonium phosphomolybdate suspension, and on the other hand, the positive electrode surface will be covered by ammonium phosphomolybdate after filter pressing. After sintering, the ammonium phosphomolybdate will form a lithium molybdate ion conductor layer on the positive electrode surface, which accelerates the transmission of lithium ions at the interface, and at the same time can protect the contact between the ternary material and the electrolyte, and reduce the generation of side reactions. Therefore, the preparation method provided by the present invention can simultaneously realize the construction of the alkali reduction and surface protection functional layer, improve the electrochemical performance of the material, and obtain the same type of positive electrode material with better electrochemical performance than the existing preparation method.
[0017] It should be noted that the ratio of ammonium phosphomolybdate and common high-nickel ternary positive electrode material should be within the range required by the present invention. If the amount of ammonium phosphomolybdate is too much, the coating effect will be affected and the capacity will be affected.
[0018] The specific preparation method is: S1. Provide common high nickel ternary positive electrode materials Ordinary high-nickel ternary positive electrode materials can be purchased directly, or the positive electrode materials can be prepared by oneself. If the positive electrode materials are prepared by oneself, the preparation method includes, for example: First, a high nickel hydroxide precursor, such as Ni x Co y Mn 1-x-y (OH)2, where x≥0.8 and 0<y≤0.2.
[0019] The precursor is mixed with a lithium source (lithium hydroxide) and then sintered to obtain a common high-nickel ternary positive electrode material.
[0020] S2. Preparation of ammonium phosphomolybdate suspension Ammonium phosphomolybdate is added into pure water and dispersed by ultrasonic stirring to form a suspension.
[0021] S3, washing and alkali reduction Add the purchased common high-nickel ternary positive electrode material or the common high-nickel ternary positive electrode material prepared in step S1 to the ammonium phosphomolybdate suspension, stir and mix for 1 to 5 minutes, and then filter at a pressure of 0.3 to 0.5 MPa for 1 to 10 minutes.
[0022] It should be noted that the stirring and mixing time should not be too long, otherwise lithium dissolution will occur. Therefore, the stirring and mixing time needs to be controlled within the range required by the present invention, and the filter press is performed immediately after the mixing is completed.
[0023] After filtration, the solid is vacuum dried at a drying oven temperature of 100-150°C.
[0024] S3, Sintering The dried product is placed at 500-600°C and sintered in the presence of oxygen for 5-10 hours to obtain a low residual alkali and high nickel positive electrode material.
[0025] An embodiment of the present invention provides a low residual alkali high nickel positive electrode material, which is prepared by the preparation method provided by the embodiment of the present invention.
[0026] An embodiment of the present invention provides a positive electrode, wherein the active component thereof includes the positive electrode material provided by the embodiment of the present invention.
[0027] A battery provided by an embodiment of the present invention includes the positive electrode provided by an embodiment of the present invention.
[0028] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0029] The following examples and comparative examples all use unwashed LiNi 0.92 Co 0.05 Mn 0.03 O2 positive electrode material is a common high-nickel ternary positive electrode material.
[0030] Example 1 Add 3 g of ammonium phosphomolybdate to 1000 g of pure water and stir to disperse it by ultrasonic to form a suspension; 1000 g of common high-nickel ternary positive electrode material was added to the above suspension, washed and stirred for 1 min, and then filtered at 0.4 MPa for 3 min to obtain a solid material; The solid material obtained by filtration was placed in a drying oven for vacuum drying at a temperature of 120°C; The dried product was sintered at 550°C in an oxygen atmosphere for 6 hours to obtain a low residual alkali and high nickel ternary positive electrode material.
[0031] Example 2 The present embodiment is substantially the same as Example 1, except that the amount of ammonium phosphomolybdate used is 6 g.
[0032] Example 3 The present embodiment is substantially the same as Example 1, except that the amount of ammonium phosphomolybdate used is 12 g.
[0033] Example 4 This embodiment is substantially the same as embodiment 1, except that 3 g of ammonium phosphomolybdate is added to 2000 g of pure water.
[0034] Comparative Example 1 This comparative example is substantially the same as Example 1, except that the amount of ammonium phosphomolybdate used is 20 g.
[0035] Comparative Example 2 This comparative example is basically the same as Example 1, except that the washing and stirring time is 5 minutes.
[0036] Comparative Example 3 This comparative example is substantially the same as Example 1, except that the ammonium phosphomolybdate suspension in Example 1 is replaced by an equal amount of water.
[0037] Comparative Example 4 This comparative example is substantially the same as Example 1, except that the ammonium phosphomolybdate in Example 1 is replaced by 4.1 g of molybdenum oxide (MoO3).
[0038] Comparative Example 5 Unwashed LiNi 0.92 Co 0.05 Mn 0.03 O2 positive electrode material.
[0039] Experimental example (1) The residual alkali amount on the surface of the positive electrode material prepared in each embodiment and comparative example was tested by first weighing 5 g of the positive electrode material and 95 g of pure water and dissolving them in a beaker, and placing the beaker on a magnetic stirrer and stirring for 20 min, filtering to obtain a filtrate, taking 10 mL of the filtrate and titrating it with a 0.05 mol / L standard solution HCl, and calculating the amounts of LiOH and Li2CO3. The test results were recorded in Table 1. (2) The positive electrode materials prepared in each embodiment and comparative example were made into positive electrode sheets and assembled into batteries to measure their electrochemical properties.
[0040] The preparation method of the positive electrode sheet is specifically to prepare a slurry with a ratio of positive electrode material: SP: PVDF = 90:5:5, and obtain a positive electrode material sheet after coating, drying and rolling; The preparation method of the battery is specifically to assemble the positive electrode material pole piece, the negative electrode, the separator, the electrode liquid, and the battery shell into a button battery with a model of CR2025.
[0041] The test conditions are 3.0-4.3V, 25℃ test conditions, and the battery's discharge capacity at 0.1C (nominal capacity is 200mAh / g), initial efficiency and 1C cycle performance (high temperature of 45℃) are evaluated.
[0042] The measured electrochemical performance data are recorded in Table 2.
[0043] Table 1 Residual alkali of positive electrode materials prepared in various embodiments and comparative examples
[0044] It can be seen from Table 1 that the residual alkali content on the surface of the positive electrode material prepared in each embodiment of the present invention is significantly lower than that in Comparative Example 5, indicating that the method provided by the present invention can reduce the residual alkali content on the surface of the high-nickel positive electrode material.
[0045] Table 2 Electrochemical performance of batteries made of materials from various examples and comparative examples
[0046] As can be seen from Table 2, compared with the positive electrode material washed with ordinary water (Comparative Example 3) and the positive electrode material not washed (Comparative Example 5), the positive electrode material prepared in each embodiment of the present invention has better capacity and cycle performance. The reason is that the ionic conductor lithium molybdate generated after coating sintering not only prevents the side reaction between the electrolyte and the positive electrode material, but also accelerates the surface lithium ion transmission.
[0047] Comparing Comparative Example 1 with the embodiments, the discharge capacity of Comparative Example 1 is significantly worse, which indicates that the coating layer of Comparative Example 1 is too thick due to excessive use of ammonium phosphomolybdate, thereby gradually reducing its capacity.
[0048] Comparing Comparative Example 2 with Example 1, the discharge capacity and cycle performance of Comparative Example 2 are significantly worse, which indicates that the washing time is too long, which will cause a large amount of lattice Li to escape, thereby deteriorating the capacity and cycle performance.
[0049] Comparing Comparative Example 4 with Example 1, the discharge capacity of Comparative Example 4 is relatively low, indicating that if molybdenum oxide is directly coated, compared with the coating with ammonium phosphomolybdate in the present application, there is still a small amount of lithium phosphate ion conductor on its surface, and the presence of the lithium molybdate and lithium phosphate dual ion conductor layer leads to a higher capacity.
[0050] In summary, the preparation method provided by the embodiment of the present invention, on the one hand, reduces the residual alkali on the surface of the high-nickel positive electrode through the ammonium phosphomolybdate suspension, and on the other hand, the positive electrode surface will be covered by ammonium phosphomolybdate after filter pressing. After sintering, ammonium phosphomolybdate will form a lithium molybdate ion conductor layer on the positive electrode surface, accelerating the transmission of lithium ions at the interface, and at the same time protecting the contact between the ternary material and the electrolyte, reducing the generation of side reactions. Therefore, the preparation method provided by the present invention can simultaneously realize the construction of the alkali reduction and surface protection functional layer, improve the electrochemical performance of the material, and obtain the same type of positive electrode material with better electrochemical performance than the existing preparation method.
[0051] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a low residual alkali high nickel positive electrode material, characterized in that: include: A common high-nickel ternary positive electrode material is mixed and stirred with an ammonium phosphomolybdate suspension to obtain a solid-liquid mixture, and then a solid in the solid-liquid mixture is extracted; The obtained solid is sintered under oxygen conditions to obtain a low residual alkali and high nickel positive electrode material; The chemical formula of the common high-nickel ternary positive electrode material is LiNi x Co y Mn 1-x-y O2, where x ≥ 0.8, 0 < y ≤ 0.2; The chemical formula of the ammonium phosphomolybdate is (NH4)3[PMo 12 O 40 ·6H2O]; The mass ratio of the ammonium phosphomolybdate to the common high-nickel ternary positive electrode material is 3-12:1000; The mixing and stirring time of the common high-nickel ternary positive electrode material and the ammonium phosphomolybdate suspension is 1 to 5 minutes.
2. The preparation method according to claim 1, characterized in that: The method of extracting the solid in the solid-liquid mixture includes: filtering to obtain filter material, and drying the filter material.
3. The preparation method according to claim 2, characterized in that: The filtration pressure is 0.3~0.5MPa, and the filtration time is 1~10min.
4. The preparation method according to claim 2, characterized in that: The drying temperature is 100~150℃.
5. The preparation method according to claim 1, characterized in that: The sintering temperature is 500~600℃ and the time is 5~10h.
6. A low residual alkali high nickel positive electrode material, characterized in that: The method is prepared according to any one of claims 1 to 5.
7. A positive electrode, characterized in that Its active component includes the positive electrode material as claimed in claim 6.
8. A battery, characterized in that: Comprising the positive electrode as claimed in claim 7.
Citation Information
Patent Citations
Method for the preparation of high activity phosphomolybdic acid based catalysts
CA1191828A
Modified low residual alkali type high nickel ternary cathode material and preparation method and application thereof
CN109768254A
Washing method of high-nickel positive electrode material and product and application thereof
CN112186157A
Multi-oxide coated ternary lithium ion battery positive electrode material and preparation method thereof
CN112661205A
Method for preparing phosphomolybdic acid modified high-nickel single-crystal positive electrode material
CN113066980A